2019
DOI: 10.1088/1742-6596/1282/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Support vector machines for classification of low birth weight in Indonesia

Abstract: This paper proposes support vector machines (SVMs), which is currently one of the most popular algorithms in machine learning (ML), in order to classify the low birth weight (LBW) data. The main objectives of this study are to predict the classification of LBW data in Indonesia based on the SVMs andto compare the performance of the proposed SVMs with the binary logistic regression as the most common model for classification of LBW data. The obtained samples were based on the results of Indonesian Demographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Recently, the applications of ML in the field of public health have increased day by day. Some works on ML were used for prediction of different fields as malnutrition [ 22 – 24 ], anemia [ 25 – 27 ], diabetes [ 28 ], low birth weight [ 29 32 ], child mortality [ 33 35 ], and so on. There was also some work on ML for prediction of underweight [ 22 – 24 , 36 , 37 ], stunted and wasted [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the applications of ML in the field of public health have increased day by day. Some works on ML were used for prediction of different fields as malnutrition [ 22 – 24 ], anemia [ 25 – 27 ], diabetes [ 28 ], low birth weight [ 29 32 ], child mortality [ 33 35 ], and so on. There was also some work on ML for prediction of underweight [ 22 – 24 , 36 , 37 ], stunted and wasted [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on statistical learning theory, this algorithm can be applied to all linear and nonlinear classification problems. In classification, linear or non-linear (Kernel type) functions are used based on the structure of the process ( Noble, 2006 ; Eliyati et al, 2019 ). SVM basically tries to separate two classes with a line or plane.…”
Section: Methodsmentioning
confidence: 99%
“…Although these studies achieved remarkable ML model performance on a small imbalanced data set, the results could be misleading and biased toward the majority class (ie, non-LBW) owing to the data imbalance issue causing them to learn based on the error rate without considering the class distribution. The studies in the second group used larger imbalanced data sets but still did not apply any rebalancing methods to their imbalanced data sets [22,23,[27][28][29]34]. Their high accuracy and low area under the receiver operating characteristic curve (AUROC) scores revealed that misleading performance remains a persistent issue [33].…”
Section: Related Workmentioning
confidence: 99%